Polymeric Nanomedicines in Diabetic Wound Healing: Applications and Future Perspectives - Chen Z; Chan K; Li X; Gong L; Ma Y; Huang C; Lu Y; Wang L; Piao C (International Journal of Nanomedicine)
Zeyao Chen,1 Kakei Chan,1 Xin Li,1,2 Li Gong,3 Yingjie Ma,4 Chiwen Huang,5 Yan Lu,6 Li Wang,1 Chunli Piao1 1Department of Endocrinology, Shenzhen Hospital (Futian) of Guangzhou University of Chinese Medicine, Shenzhen, People’s Republic of China; 2Department of Gynecology, Shenzhen Hospital (Futian) of Guangzhou University of Chinese Medicine, Shenzhen, People’s Republic of China; 3Department of Diabetes, Shenzhen Bao’an Chinese Medicine Hospital, Guangzhou University of Chinese Medicine, Shenzhen, People’s Republic of China; 4First Clinical Medical College, Shandong University of Traditional Chinese Medicine, Jinan, People’s Republic of China; 5Faculty of Science, The University of Queensland, Brisbane, Queensland, Australia; 6Research Centre of Basic Integrative Medicine, School of Basic Medical Sciences, Guangzhou University of Chinese, Guangzhou, People’s Republic of ChinaCorrespondence: Chunli Piao, Shenzhen Hospital (Futian) of Guangzhou University of Chinese Medicine, Shenzhen, 518000, People’s Republic of China, Tel +86-18819075590, Email pcl2013@sina.cnAbstract: The management of diabetic wound continues to pose significant clinical obstacles, primarily attributed to bacterial infections, excessive inflammation, oxidative stress, and impaired angiogenesis. These pathological factors not only severely affect patient well-being but also create considerable burden on medical services. Current managements often show limited efficacy, necessitating the exploration of alternative therapeutic strategies. Polymeric nanomedicines (PNs), owing to their nanoscale properties, enhanced cellular uptake, stability, bioavailability, and biocompatibility, have been broadly utilized for diabetic wound treatment. PNs demonstrate remarkable capabilities in microbial inhibition, inflammation regulation, oxidative stress mitigation, and vascular network formation, particularly when combined with various agents, including organic substances (eg, exosomes), inorganic substances (eg, metals), and biomaterials (eg, chitosan, hyaluronic acid, and hydrogels). This article systematically examines recent progress in PN-based interventions for diabetic wound recovery, highlighting the pivotal role of PNs in mitigating bacterial infection, modulating inflammatory responses, and promoting cellular regeneration. Additionally, we provide a novel perspective on the multifunctionality of PNs and their potential for overcoming the limitations of conventional therapies. Overall, PNs represent an innovative and promising approach to diabetic wound management, outperforming conventional therapies in stability, targeted delivery, and multifunctionality. In the future, investigations should concentrate on refining PNs formulations and administration strategies so as to enhance biocompatibility, and conducting well-designed clinical trials to validate their therapeutic efficacy.Keywords: polymeric nanomedicines, nanotechnology, diabetic wounds healing, drug delivery